Speak up series: Sarawak Malay dialect for non Sarawakian - Abd Samad, Sabariah; Ibrahim, Imilia; Omar, Sharifah Anom; Che Abu Shafie, Asmalini; Daud, Mohd Shamsul (Universiti Teknologi MARA, Kedah, 2019)
Language is an important channel for information transmission from one person to another. Through language we could understand people’s culture, lifestyle and attitude towards their environment. By learning language, we allow ourselves to learn and adapt the lifestyle of an ethnic. According to International Federation of Library Association (IFLA), “A network of language experts and speakers of indigenous languages have suggested that one language is being lost to the world every three months” (IFLA. org). Sarawak located in Borneo have diversity and multiracial sub ethnic. Due to the ethnic diversity, they have multi-racial people and languages. For the local Sarawakian such as Iban, Bidayuh and other ethnics, they have no problem understanding each other dialect. However, for a Non-Sarawakian or foreigners, it is challenging for them to start their life in Sarawak without learning the local dialect. Although Bahasa Melayu has become the national language and used or known by almost every Malaysian, however Bahasa Melayu Sarawak is slightly different. For anyone who never come to Sarawak or new students who further their studies here, they will face a bit puzzling to mix around with the local. Introducing Bahasa Melayu dialects will give a lots of benefits to both local as well as Non-Sarawakian. This dialects has been chosen for Speak Up Series because the dialect is widely used and understood by most of the people in Sarawak. Those who learn the language, will automatically learn the culture. The objective of Speak Up Series to introduce the local dialect to foreigners or Non-Sarawakian. Besides that, our objective is to help new students other people to speak the dialect in the local way. Speak Up Series is a handy guidebook and easy to be used. It is small, handy and full of useful information. Speak up series is an important tool to be used by anyone who loves to learn a local dialect. Students, visitors or even foreigners will be able to start and enjoy their stay in Sarawak. Just learn and be like the local people.